A study of overload effect on fatigue crack propagation using EBSD, FIB–DIC and FEM methods. (November 2016) - Salvati, E.; O'Connor, S.; Sui, T.; Nowell, D.; Korsunsky, A.M.
Abstract: Abrupt increase in the maximum load during fatigue cycling modifies the deformation conditions at the crack tip, causing plastic flow that may lead to crack closure, introducing residual stress and hardening. The net consequence of these effects is notable crack growth retardation. Despite decades of research in the field, controversy persists regarding the role of each specific mechanism and their interaction. Resolving these issues with the help of experimental observation is related to the difficulty of obtaining local residual stress information at appropriate resolution. The present study examines the effect of overload on fatigue crack grown in a Compact Tension (CT) specimen of aluminium alloy AA6082 (BS HE30). Fatigue crack was grown in the sample under cyclic tension ( R = 0.1). After the application of a single overload cycle, fatigue loading was recommenced under previous cycling conditions. The crack morphology was investigated using Scanning Electron Microscopy (SEM). Electron Backscattered Diffraction (EBSD) was used to map grain orientation and crystal lattice distortion (pattern quality) in the vicinity of the crack. EBSD analysis of intra-granular misorientation allowed the qualitative analysis of the region around the crack tip location at the time of the overload application. Observations are discussed with a view to identify the roles of crack closure and residual stress effects. Residual stress was evaluated at salient locations around the crack retardation site using the FIB–DIC method which combines the use of Focused Ion Beam (FIB) and Digital Image Correlation (DIC) for residual stress measurement at the (sub)micron-scale. The residual stress field due to overload occurrence was also simulated using Finite Element Method (FEM), and the results compared with experimental observations.